ALTERNATIVE DISPUTE RESOLUTION IN ISLAMIC BUSINESS PRACTICES OUTSIDE OF COURT - Harahap, Muttaqin; Asdhie Kodiyat MS, Benito (NOMOI Law Review, 2024)
Using non-litigation methods to resolve business disputes has long been an option. This is because the litigation process in court takes a long time and is a complicated procedure, has a win-lose nature that is not yet able to embrace common interests, tends to give rise to new problems, requires expensive costs and is unresponsive. As a general rule, people are involved in sharia economic disputes and want to resolve all conflicts that arise quickly, efficiently and cheaply. The parties to a dispute are free to choose the method of dispute resolution and the applicable law in accordance with the agreed agreement, but may face many obstacles in reaching an agreement. One of them is by resolving disputes through a body that has been formed by the Indonesian Ulema Council, namely the National Sharia Arbitration Board. Arbitration institutions can resolve problems quickly and precisely, the results of arbitration decisions are absolute and cannot be intervened by the court and there are no territorial restrictions in resolving disputes, therefore many entrepreneurs and business people tend to choose the arbitration route. The aim of this research is to determine alternatives for dispute resolution in Islamic business practices outside the court. This type of research and approach is normative research using a normative juridical legal research approach. National Sharia Arbitration Board has the authority to resolve fairly and quickly muamalah (civil) disputes arising in the fields of trade, finance, industry, services and others which according to law and statutory regulations are fully controlled by the disputing party, and the parties agree in writing to submit the settlement to the National Sharia Arbitration Board in accordance with the procedures of the National Sharia Arbitration Board.